Critical success factors in housing industries in Kubang Pasu, Kedah - Mohamad, Nurzaini; Vikneswaran, Humithra Devi Suguna; Tan, Kah Yen; Yahya, Halimatun Shazwani; Teoh, Yi Fung; Mohd Zahari, Fadhilah (2015)
The housing industry is a vital sector both to country economy and the citizenship welfare. However, there are many issues of the housing industry limiting the growth of the industry. For instance, income of the housing industry decreases day by day due to some issues compared to other sectors.Reflecting through differences in market segments, there are many factors that influence the success of housing industries which mostly circle around economics, demographic, geographic and many more.For that, this research investigates the five existing critical success factors on housing industry in Kubang Pasu.This research will use a survey to gather potential customer perceptions and perspectives into the analysis.It is expected that the findings could contribute towards greater understanding in view of housing industry.This research is also expected to provide good insights on managerial applications.